2006
DOI: 10.1111/j.1365-2559.2006.02430.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation marker MCM2, but not Ki67, is helpful for distinguishing between minimally invasive follicular carcinoma and follicular adenoma of the thyroid

Abstract: MCM2, but not Ki67, is a helpful marker for differentiating MIFC from FA. The tumour cell proliferative activity supports the histological criteria based on diagnosing MIFC by either capsular or vascular invasion only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…In the case of well differentiated tumors, lower, but overlapping, values between groups were noted in our study. No significant difference in MIB-1 index between follicular tumors (FTA, atypical FTA, FTC) was observed, in agreement with some studies from immunohistochemical studies (9,21). Nevertheless, significant differences in MIB-1 index between benign and malignant follicular tumors have been presented by others (19,22,23).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In the case of well differentiated tumors, lower, but overlapping, values between groups were noted in our study. No significant difference in MIB-1 index between follicular tumors (FTA, atypical FTA, FTC) was observed, in agreement with some studies from immunohistochemical studies (9,21). Nevertheless, significant differences in MIB-1 index between benign and malignant follicular tumors have been presented by others (19,22,23).…”
Section: Discussionsupporting
confidence: 80%
“…MIB-1 proliferation index, has been studied in many types of tumors and is commonly found to be of significant prognostic value (8). In thyroid specimens, several immunohistochemistry studies have suggested that MIB-1 index has no additive diagnostic value (9,10). However, we recently carried out a study on 30 PTC patients by evaluating their clinical follow-up and post-operative MIB-1 index.…”
Section: Introductionmentioning
confidence: 99%
“…Reports of these genes were also seen in related studies of EC in China and overseas [16][17][18][19] . The functions of these genes are mainly involved in DNA replication, transcription regulation, enzymatic reactions, and the roles in cell differentiation, movement, adhesion and anti-apoptosis, etc [20][21][22][23] . Further studies on the functions of these genes in development and invasion by the EC are expected.…”
Section: Discussionmentioning
confidence: 99%
“…Sir : Several markers have been tried to help to differentiate prognostically relevant subgroups of follicular thyroid neoplasms; one of the latest was recently published in Histopathology 1 . This paper highlights the proliferation profiles (differences in MCM2 and Ki67 expression) and the topographical distribution of these markers in follicular thyroid neoplasms diagnosed by World Health Organization criteria 2 .…”
Section: Ki67 and Isel Indices By Topographical Compartments In Follmentioning
confidence: 99%
“…The immunoexpression was scored on the basis of positive nuclei staining homogeneously for MCM2 or Ki67 and assessing tumour cells in the peripheral and central part of each tumour. The authors reported no correlation between MCM2 and Ki67 (Spearman's correlation coefficient r = 0.149) and MCM2 expression predominated in peripheral tumour cells in most of the minimally invasive follicular thyroid carcinomas (FTC), whereas it was diffuse with no apparent topographical differences in many follicular thyroid adenomas (FTA) 1 …”
Section: Ki67 and Isel Indices By Topographical Compartments In Follmentioning
confidence: 99%